O resgate da memória da companhia de teatro do Instituto de Psiquiatria da UFRJ / The rescue of the memory of the UFRJ Psychiatric Institute theatre company - Corbella, Lucrecia (Cadernos Brasileiros de Saúde Mental/Brazilian Journal of Mental Health, 2012)
Este artigo tem como objetivo principal levantar a memória do grupo Andarilhos Mágicos. Esta companhia de teatro funcionava na década de 1990 no Teatro Qorpo-Santo do Hospital-Dia do Centro de Atenção Psicossocial do Instituto de Psiquiatria (IPUB) da Universidade Federal do Rio de Janeiro (UFRJ). O idealizador do projeto, o psiquiatra Raffaele Infante, inspirado em Franco Basaglia, Franco Rotelli e Jacob Levy Moreno, concebeu os princípios teóricos e metodológicos desta experiência que tinha como propósito realizar, através do teatro, a inclusão social da loucura. Este projeto na área da Saúde Mental, inserido na dimensão sócio-cultural da Reforma Psiquiátrica Brasileira, tornou-se pioneiro por realizar um trabalho artístico que ultrapassa os limites do espaço físico do Instituto de Psiquiatria: a) ao aliar no grupo usuários e não-usuários em seu processo de criação e em suas performances; b) por realizar apresentações em diversos espaços da cidade, inclusive em centros culturais de grande porte. ABSTRACT: This article aims to rescue the memories of the Andarilhos Mágicos group. This theater company worked in the 1990s in the Theatre Qorpo Santo of the Institute of Psychiatry (IPUB) Psychosocial Care Center Dat-Hospital of the Federal University of Rio de Janeiro (UFRJ), Brazil. The creator of the project, the psychiatrist Raffaele Infante, inspired by Franco Basaglia, Franco Rotelli, and Jacob Levy Moreno, conceived the theoretical and methodological principles of this experience that intended to accomplish, through the theater, the social inclusion of madness. This mental health project, inserted on the socio-cultural dimension of the Brazilian Psychiatric Reform, was a pioneer for doing artwork that go beyond the physical space of the Institute of Psychiatry: a) by integrating users and nonusers of the service in the process of creation and in their performances; b) by making presentations at various venues in the city, including prominent cultural centers. KEYWORKS: Theater. Andarilhos Mágicos. Madness. Psychiatric reform.